Evaluation of the effects of significant factors and interactions on the enrichment of arsenic and chromium by pipette tip solid phase extraction using novel P-ZrO2CeO2ZnO nanoparticles/alginate beads - Hokonya, Nichodimus; Mahamadi, Courtie; Muchanyereyi, Netai Mukaratirwa; Gutu, Timothy (European Journal of Chemistry, 2022)
The study seeks to determine the most significant factors affecting arsenic and chromium enrichment using novel P-ZrO2CeO2ZnO nanoparticles/alginate beads in order to minimize the total number of runs needed to successfully run the experiment. The effects of interactions between factors were also evaluated so that the optimum conditions which are not affected by the other factors are chosen for the experiments. The most significant factors on arsenic and chromium enrichment were screened for by using a half-factorial design, followed by the optimization of significant factors using the full-factorial design, and the interaction between factors was determined using ANOVA and interaction plots. The most significant factors for chromium recovery were sample volume, eluent flow rate, and sorbent dosage. For both chromium and arsenic recovery, interactions occurred between sample volume, dosage, and pH. The optimum conditions chosen for the experiment that gave favourable results for both metal ions were sample volume 5 mL, dosage 40 mg, pH = 7 and eluent flow rate 1 mL/min. This study showed that a preliminary screening step for the most significant factors for arsenic and chromium enrichment helps to reduce the number of total runs, and for the same experiment interactions between factors were present; hence, it is necessary to take this into account during the experimental design.